<span>Simplifying:
2x2 + -8x + -90 = 0
Reorder the terms:
-90 + -8x + 2x2 = 0
Solving
-90 + -8x + 2x2 = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '2'.
2(-45 + -4x + x2) = 0
Factor a trinomial.
2((-5 + -1x)(9 + -1x)) = 0
Ignore the factor 2.
Subproblem 1:
Set the factor '(-5 + -1x)' equal to zero and attempt to solve:
Simplifying
-5 + -1x = 0
Solving
-5 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '5' to each side of the equation.
-5 + 5 + -1x = 0 + 5
Combine like terms:
-5 + 5 = 0
0 + -1x = 0 + 5
-1x = 0 + 5
Combine like terms:
0 + 5 = 5
-1x = 5
Divide each side by '-1'.
x = -5
Simplifying
x = -5
Subproblem 2:
Set the factor '(9 + -1x)' equal to zero and attempt to solve:
Simplifying
9 + -1x = 0
Solving
9 + -1x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + -1x = 0 + -9
Combine like terms:
9 + -9 = 0
0 + -1x = 0 + -9
-1x = 0 + -9
Combine like terms:
0 + -9 = -9
-1x = -9
Divide each side by '-1'.
x = 9
Simplifying
x = 9
Solution
x = {-5, 9}</span>
The function that best defines this arithmetic sequence is:
<h3>What is an arithmetic sequence?</h3>
- In an <em>arithmetic sequence,</em> the <u>difference between consecutive terms is always the same</u>, called common difference d.
The recursive function that defines the sequence is:
- In which is the first term.
In this problem, the sequence is: {9, 5, 1, -3}
- Each term is the previous term subtracted by 4, hence .
- The first term is 9, hence .
Hence, the function is:
You can learn more about arithmetic sequences at brainly.com/question/6561461
-3x + 18 = 7x
3x + (-3x) + 18= 7x + 3x
18 = 10x
18 10x
— = —
10 10
1.8 = x
Answer:
Maby b
Step-by-step explanation:
sorry if wrong
<h2>
Hello!</h2>
The answer is:
They spent $176 together.
<h2>
Why?</h2>
We are given an expression which represents the money spent for each girl, it's a function of time and it will show how much they can spend in terms of hours.
Assuming that you have committed a mistake writing the equation, otherwise, the given options would not fit, the expression is:
Now, from the statement we know that the function represents how much money each girl spent, so, if we need to calculate how much money they will spend together, we need to multiply the expression by 2, so we have:
Then, calculating the spent money for 2 hours, we need to substitute the variable "x" with 2.
Calculating we have:
Hence, we have that they spent $176 together.
Have a nice day!